Joint hybrid precoder and combiner design for multi-stream transmission in mmWave MIMO systems - Li, Ming; Wang, Zihuang; Tian, Xiaowen; Liu, Qian (IET communications, 2017)
Millimeter wave (mmWave) communications have been considered as a key technology for future 5G wireless networks since it can provide orders-of-magnitude wider bandwidth than current cellular bands. To overcome the severe propagation loss of the mmWave channel, an economic and energy-efficient analogue/digital hybrid precoding and combining transceiver architecture is widely used in mmWave massive multiple-input multiple-output (MIMO) systems. The digital precoding/combining layer offers more freedom than pure analogue one and enables multi-stream transmission. In this study, the authors consider the problem of codebook-based joint hybrid precoder and combiner design for multi-stream transmission in mmWave MIMO systems. The authors propose to jointly select an analogue precoder and combiner pair for each data stream successively, which can maximise the channel gain as well as suppress the interference between different data streams. Then, the digital precoder and combiner are computed based on the obtained effective baseband channel to further mitigate the interference and maximise the sum-rate. Both fully-connected and partially-connected hybrid beamforming structures are investigated. Simulation results demonstrate that the proposed algorithms exhibit prominent advantages in combating interference between different data streams and offer satisfactory performance improvements compared with the existing codebook-based hybrid beamforming schemes.